TIMELESS Suppresses the Accumulation of Aberrant CDC45·MCM2-7·GINS Replicative Helicase Complexes on Human Chromatin - Xu, Xiaohua (J Biol Chem, 2016)
The replication licensing factor CDC6 recruits the MCM2-7 replicative helicase to the replication origin, where MCM2-7 is activated to initiate DNA replication. MCM2-7 is activated by both the CDC7-Dbf4 kinase and cyclin-dependent kinase and via interactions with CDC45 and go-ichi-ni-san complex (GINS) to form the CDC45·MCM2-7·GINS (CMG) helicase complex. TIMELESS (TIM) is important for the subsequent coupling of CMG activity to DNA polymerases for efficient DNA synthesis. However, the mechanism by which TIM regulates CMG activity for proper replication fork progression remains unclear. Here we show that TIM interacts with MCM2-7 prior to the initiation of DNA replication. TIM depletion in various human cell lines results in the accumulation of aberrant CMG helicase complexes on chromatin. Importantly, the presence of these abnormal CMG helicase complexes is not restricted to cells undergoing DNA synthesis. Furthermore, even though these aberrant CMG complexes interact with the DNA polymerases on human chromatin, these complexes are not phosphorylated properly by cyclin-dependent kinase/CDC7-Dbf4 kinase and exhibit reduced DNA unwinding activity. This phenomenon coincides with a significant accumulation of the p27 and p21 replication inhibitors, reduced chromatin association of CDC6 and cyclin E, and a delay in S phase entry. Our results provide the first evidence that TIM is required for the correct chromatin association of the CMG complex to allow efficient DNA replication.